Storage study on pan de sal made from wheat-coconut flour composite - Mayo, Doris Roceta
ABSTRACT Of the four samples of pan de sal with varying levels of CRF evaluated- 0%, 4%, 8%, 12% of the total flour weight- no significant difference in terms of the various sensory attributes existed based on the evaluation of a 30-member untrained panel. Thus, 12% was considered to be the optimum level of flour substitution to produce an acceptable pan de sal. The staling pattern of four pan de sal samples- A (with 0% CRF stored at freezing temperature), B (with 0% CRF stored at room temperature), C (with 12% CRF stored at freezing temperature), and D (with CRF stored at room temperature)- were determined for three days. The intra- and interlayer change in the moisture contents was most pronounced in sample B followed by sample A, D, and C, respectively. The change in water hydration capacity did not follow any clear trend but the results for the samples stored at the same temperature paralleled each other. The decrease in compressibility as greatest in sample D followed by sample B, A, and C, in that order. The results of sensory evaluation, on the other hand, reflected decreased springiness, flavor, and fineness of texture in the bread samples during storage. The change was most pronounced in sample B followed by samples D, C, and A, in that order. The bread samples were still microbially acceptable after three days of storage, in terms of the total plate and yeast and mold counts. The change was minimal although i was most notable in sample D followed by samples B, C, and A, respectively.